(untitled) (Canadian Medical Education Journal, 2021)
Implication Statement The COVID-19 pandemic resulted in changes to clinical clerkship delivery including decreased surgical exposure. The Department of Obstetrics and Gynaecology at Dalhousie University developed a novel, resident-led learning experience using a curated presentation of operative footage. This session aimed to improve medical students’ orientation to the operative environment and supplement teaching on pelvic anatomy and gynaecologic surgery in response to decreased exposure during the COVID-19 pandemic. Medical students perceived this session as valuable and felt it improved their preparedness for the operating room. This initiative has the potential to improve medical student orientation to the operative environment.